Dissemination of Student Research in a Canadian Master of Science in Physical Therapy Programme. - Salbach, Nancy M.; O'Brien, Kelly; Evans, Cathy; Yoshida, Karen (Physiotherapy Canada, 2013)
Purpose: To determine the extent of presentation and publication, as well as time to publication, of student research completed as a component of a Master of Science in Physical Therapy (MScPT) degree at a Canadian university. Method: The authors conducted a retrospective cross-sectional study of MScPT research projects completed between 2003 and 2009, each undertaken by a group of MScPT students who carried out protocol development, ethics submission, data collection, analysis, and manuscript and poster preparation under the supervision of research advisors. Research advisors were e-mailed a request for citations of presentations and publications. Results: Advisors from 102 of 113 research projects completed from 2003 through 2009 provided information, for a response rate of 90.3%. Of the 102 groups, 53.9% disseminated findings through publication or presentation, 33.3% presented at one or more conferences, and 30.4% published at least one peer-reviewed journal article. Median time to publication was 21 months. Almost half the journal articles (47%) were published in Physiotherapy Canada. Conclusions: MScPT student research groups are disseminating their findings through publication or presentation at a moderate rate. Investigation of factors influencing dissemination is needed to develop strategies to facilitate knowledge transfer.